2016
DOI: 10.21082/blpn.v20n2.2014.p77-84
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Hibrid Hasil Persilangan Mangga Arumanis-143 dengan Tiga Kultivar Mangga Merah Berdasarkan Karakter Buah

Abstract: <p>Evaluation of Mango Hybrids Derived from Crossing of Arumanis-143 with Three Red Mango Cultivars Based on Fruit Characters. Karsinah, Rebin, and Lukitariati Sadwiyanti. In order to improve the character of mango cv. Arumanis-143 that has green-skinned fruit to become red one, Indonesian Tropical Fruits Research Institute Solok had mainactivity, i.e. crossing between Arumanis-143 with Cukurgondang red clones. The objectives of this research were to evaluate the hybrids of mango cv. Arumanis-143 crossin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…Indonesia's Gadung Klonal 21, commonly known as Avomango, is a popular mango cultivar owing to its thick flesh, low fiber content, and sweet flavor. 1 Avomango can be eaten in the same way as an avocado. It was developed in Pasuruan Regency, East Java.…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia's Gadung Klonal 21, commonly known as Avomango, is a popular mango cultivar owing to its thick flesh, low fiber content, and sweet flavor. 1 Avomango can be eaten in the same way as an avocado. It was developed in Pasuruan Regency, East Java.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers reported that plastic mulch can reduce soil organic matter concentration (Karsinah, 2013;Dog et al, 2018) and soil respiration (Gao et al, 2019). Repeated application of mulch results in an increased amount of plastic residue in the agricultural sector (Liu et al, 2014;Karsinah et al, 2018), which then deteriorates and fragments during the growing season.…”
Section: Introductionmentioning
confidence: 99%
“…Pada satu dasa warsa terakhir, terjadi perubahan perilaku konsumen yang memengaruhi pasar dan industri buah mangga nasional, di antaranya adalah karakteristik buah mangga (Perwita & Saptana 2020). Hingga kini, karaktersitik buah mangga yang disukai konsumen secara umum tidak hanya menitikberatkan pada rasa, tekstur, dan aroma buah, namun juga pada karakter penampakan kulit buah yang berwarna merah (Karsinah, Rebin & Sadwiyanti 2016).…”
unclassified